IDENTIFIKASI JENIS CACAT KAYU BULAT JATI (Tectona grandis Linn. F.) PADA AREAL PEMANENAN DI KPH JEMBER - Ardhiansyah, Afthony; Tavita, Gusti Eva; M, Iskandar A (Universitas Tanjungpura, 2019)
Teak trees are high-quality plants.The activity of harvesting teak doesn’t always produce good quality or without defects found.Various types of defects will reduce the quality and selling value of wood.The purpose of this research was to identify and measure the defects of teak roundwood (Tectona grandis) in the harvesting area in KPH Jember. Knowing the type and quantity of defects is expected to be a reference for companies, especially Perum Perhutani, KPH Jember on process of maintaining teak trees during harvesting, get better results and higher value results. The method that was used in this research was quantitative descriptive research and go to the research site.Sampling is done bypurposive sampling. The research was conducted in March - April 2018. The results of the identification of teak defects (Tectona grandis Linn.F.) found 23 types of defects that was form defects , body defects, or bontos defects. The type of defect found is straightness, cylindrical, backwardness, groove defects, direction of fiber defects, inger-inger, buncak-buncak, hole gerek, broken defects, hole in the body, wood eye, lump defects, lengar defects, broken up defects, slemper defects, bontos defects, fragile terrace, rotten terrace, hole defects, gubal defects, pakah defects, gabeng defects, dan kunus defects. The most defects were the type of buncak-buncak light as 89 trees (98.89%) and 566 sortiment (56.39%) that having defects, while the least defect were type of big hole gerek as 2 trees (2.22%) and 3 sortiment (0.30%) that having defects.Keywords : defect, harvesting, identification, perhutani, teak.